FOR A CLASS OF AUTONOMOUS DYNAMICAL SYSTEMS - Piperevski, Boro M. (Matematichki Bilten, 2015)
This paper considers a class of autonomous dynamical systems in many aspects. It shows the connection with EPGLT and EPGD, associated with three type’s diffeomorphism. It studied attractor (attractors) for the solution (solutions) at some special autonomous dynamical systems classes. By that, it shows some important properties from topological and metric aspect.